Privacy and Relationships of Roommates in the Situation of Covid 19 - Paramita Sanpaychudayan; Benjamas Kutintara (Environment-Behaviour Proceedings Journal, 2023)
The lack of privacy affected the student roommates' relationships. This study investigates the relationship between privacy and roommates' relationships in the COVID-19 situation and investigates the relationship between sensitivity to the lack of privacy and relationship status among roommates during COVID-19. Data was collected by behavioral traces in 4 bedrooms, conducting interviews and focus group discussions with eight students, and distributing questionnaires to 61 students. Findings found that in COVID-19, half of the sample felt more negatively about their privacy being disturbed. Privacy and relationships were positively correlated, and relationship status did not affect sensitivity to the lack of privacy.
Keywords: COVID-19 and Mental Health; Place Attachment and Urban Studies